Blockade of TGF-β signaling reactivates HIV-1/SIV reservoirs and immune responses in vivo - Sadia Samer; Yanique Thomas; Mariluz Araínga; Crystal Carter; Lisa M. Shirreff; Muhammad S. Arif; Juan M. Avita; Ines Frank; Michael D. McRaven; Christopher T. Thuruthiyil; Veli B. Heybeli; Meegan R. Anderson; et al. (JCI Insight, 2023)
TGF-β plays a critical role in maintaining immune cells in a resting state by inhibiting cell activation and proliferation. Resting HIV-1 target cells represent the main cellular reservoir after long-term antiretroviral therapy (ART). We hypothesized that releasing cells from TGF-β–driven signaling would promote latency reversal. To test our hypothesis, we compared HIV-1 latency models with and without TGF-β and a TGF-β type 1 receptor inhibitor, galunisertib. We tested the effect of galunisertib in SIV-infected, ART-treated macaques by monitoring SIV-env expression via PET/CT using the 64Cu-DOTA-F(ab′)2 p7D3 probe, along with plasma and tissue viral loads (VLs). Exogenous TGF-β reduced HIV-1 reactivation in U1 and ACH-2 models. Galunisertib increased HIV-1 latency reversal ex vivo and in PBMCs from HIV-1–infected, ART-treated, aviremic donors. In vivo, oral galunisertib promoted increased total standardized uptake values in PET/CT images in gut and lymph nodes of 5 out of 7 aviremic, long-term ART-treated, SIV-infected macaques. This increase correlated with an increase in SIV RNA in the gut. Two of the 7 animals also exhibited increases in plasma VLs. Higher anti-SIV T cell responses and antibody titers were detected after galunisertib treatment. In summary, our data suggest that blocking TGF-β signaling simultaneously increases retroviral reactivation events and enhances anti-SIV immune responses.